Efficacy and Safety of Endoscopic Resection Followed by Chemoradiotherapy for Superficial Esophageal Squamous Cell Carcinoma: A Retrospective Study. Issue 8 (August 2017) - Hamada, Kenta; Ishihara, Ryu; Yamasaki, Yasushi; Hanaoka, Noboru; Yamamoto, Sachiko; Arao, Masamichi; Suzuki, Sho; Iwatsubo, Taro; Kato, Minoru; Tonai, Yusuke; Shichijo, Satoki; Matsuura, Noriko; et al.
Abstract : OBJECTIVES: : The reported 1‐ and 3‐year overall survival rates after esophagectomy for stage I superficial esophageal squamous cell carcinoma (SESCC) are 95–97% and 86%, and those after definitive chemoradiotherapy (CRT) are 98% and 89%, respectively. This study was performed to elucidate the efficacy and safety of another treatment option for SESCC: endoscopic resection (ER) followed by CRT. METHODS: : We retrospectively reviewed the overall survival, recurrence, and grade ≥3 adverse events of consecutive patients who refused esophagectomy and underwent ER followed by CRT for SESCC from 1 January 2006 to 31 December 2012. RESULTS: : In total, 66 patients with SESCC underwent ER followed by CRT during the study period, and complete follow‐up data were available for all patients. The median age was 67 (range, 45–82) years, and the median observation period was 51 (range, 7–103) months. Local and metastatic recurrences occurred in 2 (3%) and 6 (9%) patients, respectively, and 17 (26%) patients died. The 1‐, 3‐, and 5‐year overall survival rates were 98%, 87%, and 75%, respectively. One of the 23 patients with mucosal cancer and 5 of 43 with submucosal cancer developed metastatic recurrences ( P =0.65). Five of the 61 patients with negative vertical resection margin and 1 of 5 with positive vertical resection margin developed metastatic recurrences ( P =0.39). None of the 30 patients without lymphovascular involvement developed metastatic recurrences; however, 6 of 36 patients with lymphovascular involvement developed metastatic recurrences ( P =0.0098). Grade ≥3 adverse events occurred in 21 (32%) patients and all adverse events were associated with CRT, hematological adverse events in 13 (20%), and non‐hematological adverse events in 9 (14%). CONCLUSIONS: : ER followed by CRT provides survival comparable with that of esophagectomy or definitive CRT and has a low local recurrence rate. A particularly favorable outcome is expected for cancers without lymphovascular involvement.